Identifying research priorities for post-collision care in the United Kingdom: protocol for a road injury priority setting partnership. - Nutbeam,T; Leech,C; E,Baker C; Box,E; R,Rodgers L; Dungay,K; Johnson,L; Lee,B; MacQueen,M; Fenwick,R; Marritt,I; Dunbar,I; et al. (Scand J Trauma Resusc Emerg Med, 2025)
BACKGROUND: Road traffic injury remains a significant global health challenge, causing over 1.2 million deaths and tens of millions of non-fatal injuries each year. In the United Kingdom (UK), more than 1,600 people died and nearly 30,000 sustained serious injuries on the roads in 2024. While improvements in vehicle design, road infrastructure, emergency response, and road user behaviour have contributed to a sustained reduction in road deaths over recent decades, outcomes for those injured remain variable, and post-collision care has received comparatively less research attention. The Road Injury Chain of Survival framework identifies five interdependent stages where timely, coordinated interventions can improve survival and recovery, however, there has been no systematic effort to define the most important research questions in this area. METHODS: This protocol describes a UK-wide Road Injury Priority Setting Partnership (PSP) conducted using the established methodology of the James Lind Alliance. Research uncertainties will be gathered via a national open-access survey and supplemented by a targeted evidence scan of published research recommendations and clinical guidelines. Submissions will be collated, categorised, and checked against the current evidence base to ensure that only true uncertainties progress. A multi-stakeholder consensus workshop, using the Nominal Group Technique, will identify a 'Top 10' list of research priorities. A secondary output will map priorities to each stage of the Road Injury Chain of Survival to guide targeted research and innovation. DISCUSSION: This is the first PSP focused specifically on post-collision care in the UK. By integrating the perspectives of patients, carers, bystanders, clinicians, policymakers, and researchers, the PSP aims to produce priorities that are directly actionable and relevant to national needs. The findings will inform funders, guideline developers, and service providers, supporting more effective